Impact of the Thrombectomy Trials on the Management and Outcome of Large Vessel Stroke: Data From the Lyon Stroke Center - Viannay, Louis; Haesebaert, Julie; Florin, Fannie; Riva, Roberto; Mechtouff, Laura; Gory, Benjamin; Ong, Elodie; Labeyrie, Paul-Emile; Derex, Laurent; Hermier, Marc; Chamard, Leila; Berner, Lise-Prune; et al. (Frontiers in Neurology, 2018)
Introduction Randomized trials (RT) have recently validated the superiority of thrombectomy over standard medical care, including intravenous thrombolysis (IVT). However, data on their impact on routine clinical care remains scarce. Methods Using a prospective observational registry, we assessed: (1) the clinical and radiological characteristics of all consecutive patients treated with thrombectomy; (2) the outcome of all patients with M1 occlusion (treated with thrombectomy or IVT alone). Two periods were compared: before (2013-2014) and after (2015-2016) the publication of RT. Results Endovascular procedures significantly increased between the two periods (N=82 vs 314, p<0.0001). In 2015-2016, patients were older (median [IQR]: 69 [57-80] vs 66 [53-74]; p=0.008), had shorter door-to-clot times (69 [47-95] vs 110 [83-155]; p<0.0001) resulting in a trend towards shorter delay from symptom onset to reperfusion (232 [185-300] vs 250 [200-339]; p=0.1), with higher rates of reperfusion (71% vs 48%; p=0.0001). Conversely, no significant differences in baseline NIHSS scores, ASPECTS, delay to IVT or intracranial haemorrhage were found. In 2015-2016, patients with M1 occlusion were treated with thrombectomy more often than in 2013-2014 (87% vs 32%, respectively; p<0.0001), with a significant improvement in clinical outcome (shift analysis, lower modified Rankin scale scores: OR=1.68; 95% CI: 1.10-2.57; p=0.017). Conclusion Following the publication of RT, thrombectomy was rapidly implemented with significant improvements in intrahospital delay and reperfusion rates. Treatment with thrombectomy increased with better clinical outcomes in patients with M1 occlusion.